Do so replacement and the argument/adjunct distinction in Merge-based syntax - Shuhama, Yuji (LingBaW. Linguistics Beyond and Within, 2022)
This study provides a novel look at do so replacement within the framework of the Bare Phrase Structure theory. Unlike the previous view of do so as a monolithic VP anaphor, I argue that do so is better analyzed as do and so, separately substituting for a functional Voice head and VP, respectively. This argument is supported by the observation of VP adverbs, the locative/directional interpretation of PPs, and the analysis of voice mismatch. The study consequently presents a more refined model of VP than the previous X-bar theoretic model, as it fulfills the structural requirement between complements and adjuncts.